«Չափահասության» ամերիկյան պոեզիան. Թ. Հյուլմ, Ու. Սթիվենս, Ու. Կ. Ուիլյամս - Աշխեն Սիքայելյան (ՀՀ ԳԱԱ հրատ.)
Modernist poetry is generally considered to have emerged in the late 19th century and in the early 20* century with the appearance of Imagists. The origins of Imagism is to be found in two poems by Т. E. Hulme that were published in 1909 by the Poet’s club in London. One of the most representative American poets of the time is considered to be Wallace Stevens whose work was mediative and philosophical.The poetry of William Carlos Williams also reveals the influence of Imagism. His sympathy for ordinary things and everyday events make his poetry attractive and accessible, he finds interest and beauty in everyday objects.
Keywords: Language and Literature; American literature